Plantas de cobertura e adubação nitrogenada na cultura do algodoeiro - Ferrari, Samuel [UNESP]; Furlani Jr., Enes [UNESP]; Ferrari, João V. [UNESP]; Alberton, Janaina V. (Revista Brasileira de Ciencias Agrarias, 2012)
The fiber quality, productivity and favorable climate are considered key points for the development of the cotton crop in the Brazilian Cerrado. This study aimed to evaluate the effect of cover crops and N application in presowing on the cotton crop growth and yield. The experimental design was randomized blocks, consisting of a - three cover crops (radish, white oat and black oat) implanted during the winter period, b - four nitrogen levels (0, 30, 60 and 90 kg ha-1 of N) applied to the millet residues and before cotton sowing. In April 2008, evaluations were realized of plant development and also harvesting was performed of experimental plots of cotton plants. The results showed that the radish provides increased length of branches and cotton bolls of cotton crop, without yield increase, and the use of increasing doses of N up to 90 kg ha-1 decreased the amount of carimã per plant, increasing the number of reproductive branches and cotton yield.
Cover crops and nitrogen application on cotton
Keywords: Ammonium sulfate; Cotton yield; Gossypium hirsutum; Avena strigosa; Gossypium; Raphanus sativus